Characterization of Natural and Synthetic Sialoglycans Targeting the Hemagglutinin-Neuraminidase of Mumps Virus - Forgione, Rosa Ester; Di Carluccio, Cristina; Milanesi, Francesco; Kubota, Marie; Fabregat Nieto, Ferran; Molinaro, Antonio; Hashiguchi, Takao; Francesconi, Oscar; Marchetti, Roberta; Silipo, Alba (Frontiers in Chemistry, 2021)
The inhibition of surface viral glycoproteins offers great potential to hamper the attachment of viruses to the host cells surface and the spreading of viral infection. Mumps virus (MuV) is the etiological agent of the mumps infectious disease and causes a wide spectrum of mild to severe symptoms due to the inflammation of the salivary glands. Here we focus our attention on the hemagglutinin-neuraminidase (HN) isolated from MuV SBL-1 strain. We describe the molecular features of host sialoglycans recognition by HN protein by means of NMR, fluorescence assays and computational studies. Furthermore, we also describe the synthesis of a N-acetylneuraminic acid-derived thiotrisaccharide targeting the viral protein, and the corresponding 3D-complex. Our results provide the basis to improve the design and synthesis of potent viral hemagglutinin-neuraminidase inhibitors.